APLIKASI PUPUK TRICHO-KOMPOS PADA PERTUMBUHAN SEMAI JELUTUNG RAWA (Dyera lowii Hook.f) MENGGUNAKAN MEDIUM GAMBUT - Riana Median; M. Mardhiansyah; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Peatlands in coastal areas have complex problems related to environmental interactions in them, so they are very vulnerable to damage. Dyera lowii is one of the peat swamp endemic species and is a multipurpose tree that meets the criteria. Tricho-compost has a positive effect on plant roots, plant growth and crop production. The aim of this study was to determine the effect of Tricho-compost application on the growth of Dyera lowii seedlings and to determine the best dose of Tricho-compost on the growth of Dyera lowii seedlings on peat medium. This study used 4 treatments with tricho-compost compost at several concentration levels, namely D0 = Tricho-compost dose 0% (Control), D1 = Tricho-compost dose 20% + 80% peat soil, D2 = Tricho-compost dose 50%. + 50% peat soil, D3 = 80% Tricho-compost dosage + 20% peat soil. Data were further analyzed using variance, with SPSS software version 20.0. The application of Tricho-compost fertilizer had the effect of increasing the growth of Dyera lowii seedlings (Dyera lowii), namely the increase in plant height with a dose of 80% Tricho-compost + 20% and showed a height increase of 1.04 cm. Keywords: Dyera lowii, Tricho-kompos, peat medium.